151k views
1 vote
Solve the following system of equations: -2x + y = 1
-4x + y = -1 (1 point)

User Sph
by
6.6k points

2 Answers

0 votes
Step 1. Extract y from the first equation:

y=1+2x

Step 2. Replace y in the second equation and solve for x:

-4x+1+2x=-1

-2x=-2

x=1

Step 3. Replace x=1 in the first equation and find y:

-2 \cdot 1 + y =1

y=3




User ZeroSkillz
by
5.2k points
4 votes
-2x + y = 1....multiply by -1
-4x + y = -1
--------------
2x - y = -1 (result of multiplying by -1)
-4x + y = -1
----------------add
-2x = -2
x = -2/-2
x = 1

-2x + y = 1
-2(1) + y = 1
-2 + y = 1
y = 1 + 2
y = 3

solution is : (1,3)
User Alfonso Rubalcava
by
6.9k points